Low-voltage Gm-enhanced class-AB pseudo-differential OTA for switched-capacitor circuits - Chaloenlarp, W.; Thanachayanont, A. (My University, 2004)
A new low-voltage, rail-to-rail output swing, class-AB pseudo-differential operational transconductance amplifier (OTA) for high-speed switched-capacitor applications is proposed. Positive feedback is employed to enhance the input transconductance, which increases the open-loop DC gain and the unity-gain frequency of the OTA. Using a 0.35-μm CMOS process, the proposed OTA can obtain 78-dB DC gain, 72.5° phase margin, 100-V/μs slew rate with 1-pF load capacitor, while draining 170-μA quiescent supply current from a single 1- V power supply voltage. © 2004IEEE.
Keywords: Class-AB; Positive feedback; Pseudo-differential; Switched-capacitor